2021
DOI: 10.3390/ijerph18094706
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Post-Migration Nutrition and Lifestyle Transition and the Risk of Developing Chronic Diseases among Sub-Saharan African Migrants: A Mixed Method Systematic Review Protocol

Abstract: Sub-Saharan African (SSA) migrants face nutrition and lifestyle changes upon arrival in a host country. The shift in diet and lifestyle reflects post-migration acculturation and could predispose migrants to nutrition- and lifestyle- related chronic diseases. A mixed-methods systematic review of published studies and the grey literature on post-migration nutrition and lifestyle transition among SSA migrants will be undertaken. Studies published in English and conducted from 2000 to 2020 using quantitative and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In this sense, some research has found that immigrants, once they settle in the host country, adopt the habits of the native population, which in many cases can be harmful. One example of this can be the diet and nutrition, which is different for immigrants compared to the diet they followed in their countries of origin, and which can lead to serious health problems, some of them related to allergies [ 4 , 69 ] or more serious conditions. Those immigrants who have lived for a longer time in the host country are no longer bound to such positive selection in terms of health, as defended by the theory of “the healthy immigrant effect” [ 70 , 71 ] and can thus increase the vulnerability of suffering different diseases and modify behavioral and lifestyle patterns [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, some research has found that immigrants, once they settle in the host country, adopt the habits of the native population, which in many cases can be harmful. One example of this can be the diet and nutrition, which is different for immigrants compared to the diet they followed in their countries of origin, and which can lead to serious health problems, some of them related to allergies [ 4 , 69 ] or more serious conditions. Those immigrants who have lived for a longer time in the host country are no longer bound to such positive selection in terms of health, as defended by the theory of “the healthy immigrant effect” [ 70 , 71 ] and can thus increase the vulnerability of suffering different diseases and modify behavioral and lifestyle patterns [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immigrants’ health has been analyzed in recent studies [ 1 , 2 , 3 , 4 ]. According to the World Health Organization (WHO) (2019), health problems in immigrants are similar to those of the general population, although there is higher prevalence among certain groups and countries of origin [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies published in English from January 2000 to March 2022 were included in this review. The year 2000 was chosen as the base year due to the rapid rise in migration globally [20]. Studies were included if they were peer-reviewed and explored the barriers and/or facilitators of recruitment and/or retention of ethnic minorities, migrants and/or indigenous populations in community-based obesity prevention RCTs.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Migrants are considered a vulnerable population group for nutrition- and lifestyle-related chronic diseases due to the shift in diet patterns and lifestyle with the change in the environment [ 1 ]. Previous studies have reported a higher body mass index and waist circumference in European Asians compared to counterparts with similar cultural and genetic backgrounds in their country of origin [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported changes in food preparation methods and dietary behaviors since migration (N = 128)1 .…”
mentioning
confidence: 99%